2019
DOI: 10.1016/j.omtn.2018.11.012
|View full text |Cite
|
Sign up to set email alerts
|

An RNA Aptamer Targeting the Receptor Tyrosine Kinase PDGFRα Induces Anti-tumor Effects through STAT3 and p53 in Glioblastoma

Abstract: Human glioblastoma (GBM) is the most aggressive malignancy of the CNS, with less than 5% survival. Despite great efforts to find effective therapeutics, current options remain very limited. To develop a targeted cancer therapeutic, we selected RNA aptamers against platelet-derived growth factor receptor α (PDGFRα), which is a receptor tyrosine kinase. One RNA aptamer (PDR3) with high affinity (0.25 nM) showed PDGFRα specificity and was internalized in U251-MG cells. Following treatment with the PDR3 aptamer, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 70 publications
(80 reference statements)
0
22
0
1
Order By: Relevance
“…Aptamers have also emerged as useful targeted delivery agents for conventional drugs and small RNAs including siRNAs and miRNAs due to several advantages, such as small physical size, high stability and low immunogenicity [ 137 ]. Recently, STAT3 silencing by aptamer-siRNA chimera obtained excellent inhibition in the therapy of glioblastoma [ 138 , 139 ], suggesting that the improved oligonucleotides might offer translational potential for the treatment of solid tumors.…”
Section: Targeting Stat3 For Cancer Immunotherapymentioning
confidence: 99%
“…Aptamers have also emerged as useful targeted delivery agents for conventional drugs and small RNAs including siRNAs and miRNAs due to several advantages, such as small physical size, high stability and low immunogenicity [ 137 ]. Recently, STAT3 silencing by aptamer-siRNA chimera obtained excellent inhibition in the therapy of glioblastoma [ 138 , 139 ], suggesting that the improved oligonucleotides might offer translational potential for the treatment of solid tumors.…”
Section: Targeting Stat3 For Cancer Immunotherapymentioning
confidence: 99%
“…The improved half‐life of aptamers in vivo is suggestive of future clinical application as molecular imaging agents . Of note, aptamers themselves can be used as therapeutics in blood clotting, or local treatment, or inducing antitumor effect . Furthermore, aptamer‐mediated delivery systems have been broadly applied in cancer therapies, including aptamer‐drug conjugates, aptamer‐nanoparticle/polymer‐drug delivery system, and aptamer‐mediated cancer nucleic acid therapy .…”
Section: Aptamer Emerges As a Prominent Targeting Ligand For Nanodelimentioning
confidence: 99%
“…In the first, the STAT3 siRNA was conjugated to PDR3, an anti-PDGFRα RNA aptamer. The conjugate strengthens the effect of the aptamer alone: in fact, the authors firstly demonstrated the effect of PDR3 on apoptosis and then confirmed that PDR3-siSTAT3 mediates strong reduction in cell viability in vitro [ 42 ]. In the second, Esposito et al characterized a modified 2′F-Py nuclease-resistant RNA conjugate in vitro and in vivo.…”
Section: Resultsmentioning
confidence: 99%